Kepemimpinan Kepala Sekolah Dalam Pemberdayaan Guru di SMP Negeri 1 Kutalimbaru Kabupaten Deli Serdang - Simanjuntak, Rusnita; Prasetia, Indra (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The purpose of this study was to determine the leadership style of the principal of SMP Negeri 1 Kutalimbaru and the empowerment carried out by the principal of SMP Negeri1 Kutalimbaru. This research uses a qualitative approach method. The data collection technique of this research is through observation, interview, documentation and questionnaire. The results showed that the principal of SMP Negeri 1 Kutalimbaru applied democratic leadership in carrying out his duties, the principal made his subordinates a team to work together in running school programmes. The principal always supports teachers to attend trainings to improve their knowledge and skills, the principal openly accepts ideas and input from subordinates. The principal gives freedom to teachers in designing appropriate learning methods, encourages teachers to share ideas and good practices such as the driving teacher in the school sharing the good practices they have obtained with teachers in SMP Negeri 1 Kutalimbaru. Teachers who have been empowered by the principal feel valued and feel more enthusiastic about attending training that will increase their knowledge and skills in learning, thus motivating students to be more active in classroom learning.